Partially preserved structure of the central shrine of the Someshwar Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is a closer view of the partially preserved structure of the central shrine of the Someshwar Mahadev Temple. The remnants of the shikhara (superstructure) are ornate. At the base of the centre of the shikhara, there is a rectangular block that acts as the surasenaka of the shikhara. Although partially preserved, it is evident that the superstructure of the garbhagriha (sanctum sanctorum) of the central shrine was of the shekhari (multi-spire) variety. The mulashringa (main spire), pratyangas (minor limbs) and angas (major limbs) of the shikhara have intricate gavaksha (dormer windows) ornamentations.